Pengaruh Mekanisme Corporate Governance dan Kualitas Kantor Akuntan Publik Terhadap Integritas Laporan Keuangan - Defriandio Rahiim; Sholiyah Wulandari (Esensi: Jurnal Bisnis dan Manajemen, 2014)
The purposes of this research was to analyze the effect of corporate governance mechanisms and the quality of public accounting firms on the integrity of financial statements. This research used a sample of companies listed on the Indonesia Stock Exchange during the period 2009 to 2011. Number of manufacturing firms sampled this research were 66 companies with over 3 years of observation. Based on purposive sampling method, the total sample was 198 financial statements or annual reports. But the researchers reduced the number of samples to discard as many as 28 pieces of data outliers to improve the normality of the data, so that the end of the research the total sample is 170 financial statements or annual reports. Testing this hypothesis using multiple regression analysis. The result showed that the corporate governance mechanisms and the quality of public accounting firms have a significant effect on the integrity of financial statements.DOI: 10.15408/ess.v4i3.2436